2016
DOI: 10.3130/jaabe.15.527
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Visibility on Fear of Crime in Schools′ Interior Environments

Abstract: In any given environment, visibility is a critical element that affects fear of crime. This study provides empirical evidence of the effects of visibility on fear of crime within elementary schools using a quantitative analysis. Spots in which children felt fear were identified, and their characteristics were analyzed according to the four visibility dimensions of: visual connectivity and visual integration, each with and without visible distance restrictions. One finding was that fear of crime was high in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Studies that looked at crime prevention measures in relation to crime at an urban level produced promising, predictive, inexpensive tools. Although similar tools were used to successfully measure certain behavioral outcomes, such as navigating through elementary schools [37], or wayfinding in hospitals [38], it might be useful to use these tools to address preparedness and response time inside buildings for active shooting prevention. This pilot study is the first of its kind to explore the same tools to assess preparedness from active shooting incidents.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…Studies that looked at crime prevention measures in relation to crime at an urban level produced promising, predictive, inexpensive tools. Although similar tools were used to successfully measure certain behavioral outcomes, such as navigating through elementary schools [37], or wayfinding in hospitals [38], it might be useful to use these tools to address preparedness and response time inside buildings for active shooting prevention. This pilot study is the first of its kind to explore the same tools to assess preparedness from active shooting incidents.…”
Section: Discussion and Policy Implicationsmentioning
confidence: 99%
“…A study by Lee and Ha (2016), which identified the effect of visibility on fear of crime within elementary schools, urged capturing and consider the curvature of the surface, on the natural environment and human-made. The angle and distance of visibility are the essential elements that influenced the fear among student.…”
Section: Research Backgroundmentioning
confidence: 99%